Open source MySQL Browser for Open Innovation - Bucea-Manea-Tonis, Radu (Journal of Economic Development, Environment and People, 2014)
Abstract. Our purpose is to cross-compile MySQL driver source code for Linux on Windows architecture using a tool chain in order to build a neutral valid graphic interface on 32 bits. Once achieving this goal we could say that every possible Open source application can be built and run on Windows with maximum efficiency concerning costs and resource. This browser is an example of open innovation because its source code is free for anybody willing to develop new software apps for business and uses only Open source tools.